METHODOLOGICAL AND APPLIED PRINCIPLES OF SOCIAL RESPONSIBILITY MANAGEMENT OF BUSINESS ENTITIES - PANCHENKO, Volodymyr; PANCHENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article highlights the priority of introducing the elements of social responsibility of business into the national model of economic management and makes assumptions about obtaining economic and social benefits from such measures in building a highly developed and progressive economy. The results of the analysis of research by domestic scientists are emphasized and conclusions are drawn that attention to this issue is increasing, but it concerns certain aspects of social responsibility of business. Disagreements in the definition of social responsibility of business in the USA and European countries are highlighted and it is emphasized that they are mainly determined at the level of business-state relations. Attention is paid to the applied characteristics of the main approaches (instrumental, from the position of political influence, social requirements and ethics) to the concept of social responsibility of business. If the activities of American corporations are generally determined by their owners and managers, then European companies are significantly influenced by state authorities and professional associations, which strictly define the minimum requirements for their activities. The only difference is whether to perceive the enterprise as an open or as a closed system. As a closed system, the enterprise is not influenced by the external environment and does not interact with it. In contrast, enterprises as open systems dynamically interact with their environment. However, if we proceed from the understanding of the enterprise as a closed system, then the idea of social responsibility of business is significantly narrowed, covering only the responsibility to owners and employees. The obtained conclusions made it possible to form conceptual methodological and applied principles of social responsibility management of business, which should be paid attention to by Ukrainian state institutions and can be successfully implemented in the national business environment.